Relationship Between Bullying and Cyberbullying Victimization and Regulation Difficulties in Adolescents in Ecuador - Pino-Falconí, Marco (2024)
The present study aims to identify the relationship between bullying victimization (BV) and cyberbullying victimization (CBV) in emotional regulation difficulties (ERD) in a sample of adolescents in Ecuador. This work is based on a quantitative, descriptive, correlational, gender-comparative, cross-sectional design. The sample consisted of 384 adolescents, with 44% being females and the remaining 56% males, aged between 14 and 19 years (M= 15.7; SD= 4.4). The students came from 9 schools in two cities in Ecuador. BV and BCV levels were found to be low, while ERD levels were moderate. There were only gender differences in BV, with a higher presence in males than females. Finally, there was a positive relationship between BV (moderate), BCV (slight) and DRE. BV and BCV are also positively and moderately related. BV and BVB are elements that interact in a relevant way with DRE in adolescents in Ecuador, indicating a particular connection.